The Effect of Tranexamic Acid (Cyclokapron) on Post-Surgical Bleeding Following the Removal of Impacted Lower Wisdom Teeth in Healthy Individuals - Rayan S. Hamid; Wafaa K. Fathi; Wael T. Al Wattar (University of Mosul, College of Dentistry, 2008)
Aims: To evaluate the effect of local irrigation with tranexamic acid in minimizing post-operative bleeding following the removal of impacted lower wisdom teeth. Materials and Methods: This clinical trial was conducted at the Department of Oral and Maxillofacial Surgery / College of Dentistry / University of Mosul. The sample recruited comprised twenty healthy subjects who required surgical removal of clinically as well as radiographically evident impacted lower wisdom teeth. The sample was subdivided into two groups of ten subjects each. The first group which is the control group included ten subjects where after removal of the tooth, local irrigation of socket was carried out with normal saline. The second group which is the trial group comprised ten subjects also, but in which tranexamic acid (injectable solution) in diluted form was used for local irrigation of socket. Both solutions were of equal amount. Estimation of amount of blood loss immediately following surgery was the criterion for comparison and was based on weight of gauze used before and after application over extraction socket. Results: The results showed a statistically significant decrease in the amount of blood loss in the trial group when compared with the control group. Conclusions: Tranexamic acid as commercially available or freshly prepared oral rinse may be used as an aid for the reduction or prevention of postoperative bleeding following the removal of third molars in healthy subjects as well as in patients with bleeding problems.